Use of antibiotics in women undergoing correction of an obstetric anal sphincter injury: Results from a national Israeli survey. Issue 1 (19th June 2022) - Barg, Moshe; Rotem, Reut; Weintraub, Adi Y.; Grisaru‐Granovsky, Sorina; Michaelson‐Cohen, Rachel; Rottenstreich, Misgav
Abstract: Objective: Obstetric anal sphincter injures (OASIS) have long‐term implications on women's health. Administration of antibiotic prophylaxis and treatment following OASIS repair is controversial. We conducted a national survey to provide data about practice routines regarding antibiotic prophylaxis and treatment following OASIS repair in Israeli labor and delivery units. Methods: A national survey was performed among obstetricians and gynecologists from 24 university‐affiliated delivery centers within the jurisdiction of the Israeli Ministry of Health during 2020. Representatives from each center completed the "Google form" electronic survey. For each questionnaire item, the most common answer was chosen to represent the center's answer. Results: The number of physicians who responded per center varied from 1 to 14 (median, 3.5). Preoperative and postoperative antibiotic treatment was given in 75% and 92% of the centers, respectively. While most centers (58.3%) recommend pelvic floor physical therapy on release, recommendations about functional radiologic tests vary. In all centers, there is a designated clinic for postpartum follow‐up of OASIS. Most centers (83%) allow trial of vaginal delivery in the subsequent pregnancy, on an individual basis. Conclusion: Heterogeneity exists in managing OASIS in Israel, particularly regarding administration of antibiotics. Further studies are needed to examine the consequences of different management protocols. Synopsis: Our national survey demonstrates that despite guidelines, management of obstetric anal sphincter injuries in Israel lacks consistency, specifically regarding administration of preoperative and postoperative antibiotics.